Temporal Dispersion and Duration of the Distal Compound Muscle Action Potential Do Not Distinguish Diabetic Sensorimotor Polyneuropathy From Chronic Inflammatory Demyelinating Polyneuropathy - Alcantara, Monica; Ngo, Mylan; de la Cruz, James; Menon, Deepak; Barnett-Tapia, Carolina; Katzberg, Hans; Bril, Vera (Frontiers in Neurology, 2022)
Objective To investigate the contribution of duration and temporal dispersion (TD) of the distal compound muscle action potential (CMAP) in discriminating chronic inflammatory demyelinating polyneuropathy (CIDP) from diabetic sensorimotor polyneuropathy (DSP) and from CIDP+DSP. Methods We performed a retrospective review of patients diagnosed with CIDP, DSP and CIDP+DSP (responsive to immunotherapy) and examined differences in CMAP duration and TD at baseline. Results We included 59 subjects: 17 CIDP, 21 DSP and 21 CIDP+DSP. Of these, 16 (94.1%) CIDP, 18 (85.7%) CIDP+DSP and 1 (4.7%) DSP fulfilled the 2010 EFNS/PNS criteria for definite CIDP. There was no difference in CMAP duration or TD in all nerves (compound outcome) or in individual motor nerves. Patients with CIDP/CIDP+DSP had more conduction blocks, slower conduction velocities and more prolonged F wave latencies than those with DSP. Conclusion Measures of CMAP duration and TD were not helpful in distinguishing CIDP, DSP or CIDP+DSP patients; however, parameters such as F-wave latencies, conduction blocks or the number of demyelinating parameters were useful in this separation. Significance There are no definite nerve conduction criteria to distinguish patients with CIDP+DSP from DSP alone. Further studies focusing on measures of demyelination may provide stronger evidence to guide treatment decisions in CIDP + DSP patients.